2021
DOI: 10.3390/ph14070618
|View full text |Cite
|
Sign up to set email alerts
|

Serum Extracellular Vesicle-Derived circHIPK3 and circSMARCA5 Are Two Novel Diagnostic Biomarkers for Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most frequent and deadly human brain cancer. Early diagnosis through non-invasive biomarkers may render GBM more easily treatable, improving the prognosis of this currently incurable disease. We suggest the use of serum extracellular vesicle (sEV)-derived circular RNAs (circRNAs) as highly stable minimally invasive diagnostic biomarkers for GBM diagnosis. EVs were isolated by size exclusion chromatography from sera of 23 GBM and 5 grade 3 glioma (GIII) patients, and 10 unaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 78 publications
(91 reference statements)
0
67
0
Order By: Relevance
“…SRSF1 is an RNA-binding protein with proto-oncogenic function, being involved in angiogenesis, cell migration and tumor proliferation of several types of human neoplasms, including gliomas, malignant mesotheliomas, and breast, colorectal and prostate cancers [18,[20][21][22][23][24][25]. SRSF1 immunoexpression was positively associated with worse outcome, androgen-receptor status and Ki-67 proliferation rate in prostatic adenocarcinoma [27]; a significant correlation between SRSF1, MVD and shorter overall survival times was also found in fluoro-edenite-induced malignant mesothelioma [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SRSF1 is an RNA-binding protein with proto-oncogenic function, being involved in angiogenesis, cell migration and tumor proliferation of several types of human neoplasms, including gliomas, malignant mesotheliomas, and breast, colorectal and prostate cancers [18,[20][21][22][23][24][25]. SRSF1 immunoexpression was positively associated with worse outcome, androgen-receptor status and Ki-67 proliferation rate in prostatic adenocarcinoma [27]; a significant correlation between SRSF1, MVD and shorter overall survival times was also found in fluoro-edenite-induced malignant mesothelioma [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper we provided the first immunohistochemical evidence of the poor prognostic role of this protein in UM; in more detail, we found a statistically significant correlation between higher SRSF1 immunohistochemical expression, higher MVD levels and poorer prognosis in terms of metastatic spread and lower metastasis-free-survival in UM. Regarding the relationship between SRSF1 and MVD, previous studies demonstrated that SRSF1 had a stimulatory function on tumor angiogenesis, resulting in a switch in the pro-angiogenic/anti-angiogenic ratio of VEGFA [17][18][19][20][21]; in this regard, Barbagallo et al first reported the complex relationship between circSMARCA5, a specific subtype of circRNAs with a tumor-suppressor role, and SRSF1, demonstrating that the downregulation of circSMARCA5 along with the concomitant upregulation of SRSF1 led to increased cell migration and angiogenesis in human glioblastoma tissue and cell lines [17][18][19]. The MVD count, despite not representing the best method to evaluate tumor angiogenesis, is a semi-quantitative "surrogate" of this process [27]; accordingly, the positive correlation found in our cohort between SRSF1 and MVD led us to hypothesize that SRSF1 has a pro-angiogenic role also in UM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the existence of glioma-initiating cells (GICs) a type of glioma stem cell (GSC), mediates treatment failure, tumor recurrence, and invasive phenotypes of GBM [ 4 ]. As a carrier of oncogenes/proteins and other genetic information, exosomes are involved in the conversion of non-GSCs to GSCs and participate in stabilizing the GSC phenotypic integrity [ 5 ]. GBM is also characterized by complex and heterogeneous genotypes which limit the efficacy of drugs that target specific oncogenic signaling axes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%